Cortical deafness in multiple sclerosis. Issue 5 (May 1981) - Tabira, T; Tsuji, S; Nagashima, T; Nakajima, T; Kuroiwa, Y
Abstract : Cortical deafness in a patient with multiple sclerosis is reported. Complete recovery from total deafness was seen following stages of auditory agnosia and pure word deafness. The otological and neurophysiological studies suggested lesions in subcortical white matter. This report stresses the rarity of the condition, its subcortical origin and good prognosis.